Analysis of landfill design variables based on scientific computing. (January 2018) - Cuartas, Miguel; López, Ana; Pérez, Fernando; Lobo, Amaya
Highlights: New method for the optimization of complex systems with impact on the environment. Method based on computer simulations of all combinations of the studied variables. Systematic processing of results allows finding best design and operation practices. A study case shows impact of landfill operation variables on leachate generation. Results show the relevance of the analysed scenario to the impact of some variables. Abstract: The optimal design of waste landfills is a complex, still unsolved issue. Each design variable influences the rest and it is difficult to quantify their interactions. Recent advances in scientific computing, however, allow this problem to be approached from a new perspective. Thus, in this paper a new method is proposed for the analysis and optimization of design variables in waste landfills. This method is based on the computer simulation of multiple models and the systematic analysis of the resulting data to extract knowledge. It can be extended to the optimization of other complex systems with a direct impact on the environment. Its efficacy is tested by studying the effect of five common design variables on landfill hydrology. The main results show the benefits of temporary surface lining and intermediate covers on the volume of leachate generated. Intermediate covers, however, may jeopardize landfill stability and significantly affect the variability of the leachate flow. The case studied demonstrates the usefulness of the proposed method to improve the design and operation of waste landfills. It also shows the need to analyse multiple scenarios in order to generalize the conclusions obtained.